Response of soil fungal community structure and co-occurrence network features on plantations of limestone mountains along habitat specialization gradient - Qiu, Zhenlu; Liu, Jin; Pan, Ting; Wang, Ziwen; Shen, Yanru; Wang, Xueting; Shu, Jing (Frontiers in Microbiology, 2025)
IntroductionThis study elucidated how different plantation types in limestone mountains shape the community structure and co-occurrence networks of soil fungal habitatspecialization groups, offering a habitat-adaptation perspective on the assembly mechanisms of soil microbial diversity during ecological restoration.MethodsIn this study, we grouped soil fungi from plantations of coniferous forests (CF), mixed forests (MF) and broad-leaved forests (BF) into habitat-generalists, specialists and opportunists based on niche breadth, and examined how forest type shapes their diversity, community structure and co-occurrence networks along a habitat-specialization gradient.ResultsWe found that: (1) The number and abundance of habitat-specialists significantly exceeded those of generalists. Habitat-generalists exhibited the highest abundance and ecological niche width in BF, whereas habitat-specialists were most abundant in CF. (2) The diversity index was the highest in BF across all habitat specialization groups. Differences in community structure among forest types increased with habitat specialization, and the composition of dominant tree species significantly influenced the community structure of each group. Soil properties primarily affected the community structure of habitat generalists and opportunists between BF and other forest types. (3) The network structure of habitat specialists exhibited high modularity, while habitat generalists formed independent subnetworks with more fragile structures. CF and BF exhibited strong intra-module connections and high modularity, whereas MF displayed high intermodule connectivity, which reduced their modularity. Both within-module (Zi) and between-module connectivity (Pi) of increased with habitat specialization and the proportion of broadleaved tree species.DiscussionWe concluded that broad-leaved plantations, by increasing soil environmental heterogeneity, promoted the diversity of habitat-specialists and enhancing their network hub roles, representing the optimal strategy for optimizing below-ground biodiversity and stability in limestone mountain forest restoration.